A (ir)responsabilidade civil do Estado decorrente das limitações legais ambientais impostas ao direito de propriedade - Barini Neto, Celso (2018)
The question as to the indemnity of the right to property in the face of the institution of environmental promotion instruments is due to the force of both fundamental rights. The environment, which evolved due to a favorable agenda for international environmental protection, which ended up influencing the construction of a Federal Constitution that rightly privileges the environment, within a system of rights in which it grants the reasonability that is due to it. Through a construction whose necessity necessarily permeates the perception of an existential minimum environmental, which is not limited to the environment adequate life, but that extends to intergenerational and intragenerational respect. Property, as a fundamental right consolidated in time and adapted to social and constitutional advances, achieves a liberal right that is divided, in the subjective and objective, of the right to property and the right of property, respectively, that brings the right to if the social function as an equalized instrument of ownership, attaching to its financial objective a clear social burden, bound by the Constitution. In accordance with both fundamental rights, it is noted that the civil responsibility of the State, in its duty to indemnify before the institution of the instruments of environmental promotion, is perceived as the civil liability is striding towards an evolution, as an institute. The environmental promotion instruments, in the best terms of the legislation that instituted them, should compensate only in cases where they can achieve the economic purpose of ownership. For the analysis presented here, the research used was primarily bibliographical and documentary, using the method of qualitative and deductive approach of data analysis.